THE INFLUENCE OF COASTAL CONDITIONS TO TSUNAMI INUNDATION OF BIMA BAY, WEST NUSA TENGGARA - Yudhicara Yudhicara; Rahayu Robiana (BULLETIN OF THE MARINE GEOLOGY, 2014)
Area along the coast that includes the territorial waters of the Bima Bay, West Nusa Tenggara, is prone to tsunamis, evidenced by the historical tsunamis record in 1815 due to the volcanic eruption of Tambora, 1818, 1836 and 1992 caused by earthquakes associated with tectonic system in the north of the island of Sumbawa, and 1892 were sourced from a distant source. Based on the coastal characteristics, the research area was divided into four types of beaches, namely: Steep rocky beach; Coastal walled plain; Flat coastal mangroves; and Flat sandy beaches. According to the lateral measurement, houses were built in the plains with a minimum height difference of 0.04 m at Rababuntu beach and a maximum of 22.63 m in New Asakota area. The settlement closest distance to the coastline is 10.3 m in Rababuntu, while the farthest extent is at Kawananta 194.58 m from the shoreline. The local bathymetry range between 1 and 42.5 m, where the inside of the very shallow waters of the Bay of Bima, gradually steeper at the mouth of the bay to the open sea. This conditions will influence the wave when entering the bay. It will come with large enough speed at the mouth of the bay, spread along the coastal waters of the eastern and continue spreading to all parts with the diminishing velocity, but the height increasing when it reaches shallow water, especially in the waters of the western Gulf of Bima. Several factors can affect the amount of risk that would be caused by the tsunami, in the research area include are: (1) The research area is located in an enclosed bay; (2) The local sea floor depths around the bay is relatively shallow waters; (3) Coastal characteristics of the research area is dominated by a gently sloping beach morphology with low relief, especially in the area of ??Bajo, Rababuntu and Bontokape and other beaches in the city of Bima; (4) Residential location very close to the shoreline; (5) Minimal vegetation cover; and (6) The presence of the artificial protective are inadequate. Based on tsunami modeling using the 1992 Flores earthquake parameter which is placed perpendicular to the research area obtain the maximum tsunami height around 4-5 m at Sowa and Kolo, near to the mouth of Bima Bay, while the minimum is at Kalaki, about 0,2 m which is at the inner bay. Keywords: Tsunami, coastal characteristics, bathymetry, factors influenced to tsunami inundation. Lokasi di sepanjang pantai yang mencakup wilayah Perairan Teluk Bima, Nusa Tenggara Barat, rentan terhadap tsunami, dibuktikan oleh catatan sejarah tsunami tahun 1815 karena letusan gunung berapi Tambora, 1818, 1836 dan 1992 disebabkan oleh gempa bumi yang terkait dengan tektonik sistem di bagian utara pulau Sumbawa, dan 1892 yang bersumber dari sumber yang jauh. Berdasarkan karakteristik pantai, daerah penelitian dibagi menjadi empat jenis pantai, yaitu: Pantai terjal berbatu; Pantai datar berdinding; Pantai datar berbakau; dan Pantai datar berpasir. Berdasarkan hasil pengukuran kemiringan pantai secara lateral, rumah dibangun di dataran pantai dengan perbedaan ketinggian minimal 0,04 m di Rababuntu dan maksimal 22,63 m di daerah Asakota Baru. Jarak terdekat bangunan terhadap garis pantai adalah 10.3 m di Rababuntu, sedangkan jarak terjauh adalah di Kawananta 194,58 m dari garis pantai. Rentang batimetri di perairan Teluk Bima berkisar antara 1 dan 42,5 m. Bagian dalam Perairan Teluk Bima sangat dangkal, secara bertahap makin alam dan curam di mulut teluk hingga ke laut terbuka. Kondisi ini akan mempengaruhi gelombang ketika memasuki Teluk. Gelombang akan datang dengan kecepatan yang cukup besar di mulut teluk, tersebar di sepanjang perairan pantai timur dan terus menyebar ke seluruh bagian dengan kecepatan berkurang, namun ketinggian meningkat saat mencapai perairan dangkal, terutama di perairan barat Teluk Bima. Beberapa faktor yang dapat mempengaruhi jumlah risiko yang akan disebabkan oleh tsunami, di daerah penelitian meliputi: (1) Daerah penelitian terletak di teluk tertutup; (2) Kedalaman dasar laut di sekitar Teluk adalah perairan yang relatif dangkal; (3) Karakteristik Pantai daerah penelitian didominasi oleh pantai morfologi landai dengan relief rendah, terutama di daerah Bajo, Rababuntu dan Bontokape dan pantai-pantai lainnya di Kota Bima; (4) Lokasi perumahan sangat dekat dengan garis pantai; (5) Minimalnya vegetasi penutup; dan (6) Keberadaan pelindung buatan tidak memadai. Kata Kunci: Tsunami, karakteristik pantai, batimetri, faktor yang mempengaruhi landaan gelombang tsunami.